USAHA PENGEMBANGAN KEMAMPUAN SELF-CONTROL UNTUK MENJADI PRIBADI EFEKTIF - Frans Laka Lazar (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
Each person strives to mold himself into a mature or effective person. One of the characteristics of a mature or effective person is being able to control every emotion or impulse from within. Self-control is the ability to direct one's own behavior and suppress the various urges that exist. The impulses that appear can be controlled by means of behavioral control, cognitive control, decision control, informational control, and retrospective control. And self-control should follow ethical or moral principles, the principle of awareness, the principle of reflection, the principle of patience, and the principle of distraction towards objects or something else. The objective of this research is to examine the efforts made by individuals to develop the ability to control themselves or control emotions in their lives. To achieve this goal, the researcher conducted a literature study taken from books and journals. The results of the study show three efforts made to develop self-control abilities, namely growing self-awareness, managing one emotion, and trying to become a mature person.